Towards a Typology of Tiny Houses. Issue 3 (3rd July 2019) - Shearer, Heather; Burton, Paul
ABSTRACT: The emergent tiny house movement is gaining momentum globally, in the United States where it originated, and in countries such as Australia. Little scholarly research exists on the tiny house movement, with most information limited to social and popular media. Moreover, there is limited information on the definition of a tiny house. As an important first step in bringing a more scholarly focus, this article presents a typology of tiny houses; what is a tiny house and what defining characteristics allow a tiny dwelling to be considered a tiny house? This study involved an analysis of social media, face to face interviews with key protagonists and a questionnaire survey, to establish a preliminary classification of tiny houses. We aimed to place the movement in its wider context, and establish a foundation for future research into the movement's potential to trigger positive economic and environmental change towards more sustainable urban environments.